Actitudes ambientales en estudiantes de tercer grado en el centro rural de formación en alternancia N° 60167, quebrada de Tamshiyacu, Loreto – 2023 - Vasquez Blas, Margareth Giovanna (2024)
The purpose of the thesis was to evaluate the environmental attitudes of third-grade students at the Alternation Training Center No. 60167 in Tamshiyacu, Loreto in the year 2023. It is a quantitative research of a non-experimental, descriptive, analytical, transversal type. The primary information was obtained through the application of a structured census-type interview, related to the environmental attitudes of the students, descriptive and inferential statistics were applied with the Rho Spearman correlation test, which allowed reaching the following conclusions: The students have positive and diverse understanding of the environment, highlighting the importance of nature and the need to conserve it responsibly, they also have a strong sense of responsibility towards environmental protection. They demonstrate environmental concerns highlighting deforestation, waste management, the welfare of wild animals, water pollution and soil contamination and reducing anthropogenic environmental impact. They lack knowledge about renewable energies, but have the willingness and desire to participate. in cleaning or reforestation activities in their community. They acknowledge having received training in environmental issues and participate in activities on environmental issues and consider that environmental education will be useful in their lives. They segregate waste in their homes although some do not and the materials they recycle are plastic bottles, plastic bags, cans and organic matter. They reflect motivation and willingness to get involved in the protection and conservation of the natural environment and agree with the ban on single-use plastic products, such as bags or straws. They consider that water should be used responsibly. The correlation analysis allows us to reject the Null Hypothesis, because there is a significant correlation between environmental attitudes and learning factors. Students who show positive attitudes towards the environment have greater environmental participation and awareness.